1998
DOI: 10.1007/978-3-7091-3693-5_17
|View full text |Cite
|
Sign up to set email alerts
|

Specification and Verification of Media Constraints using UPPAAL

Abstract: The version in the Kent Academic Repository may differ from the final published version. Users are advised to check http://kar.kent.ac.uk for the status of the paper. Users should always cite the published version of record.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 5 publications
0
14
0
Order By: Relevance
“…It can be seen QoS statements such as various types of Jitter [13] are Timeliness properties of degree 1, whereas latency is a Timeliness property of degree 2. In general, it seems that, any property related to the relative time of occurrence of K events can be evaluated via a Timeliness property function of degree K. Assume that the functional behaviour of system is modelled via a network of Timed Automata.…”
Section: Definition 3 a Timeliness Property Of Degreementioning
confidence: 99%
“…It can be seen QoS statements such as various types of Jitter [13] are Timeliness properties of degree 1, whereas latency is a Timeliness property of degree 2. In general, it seems that, any property related to the relative time of occurrence of K events can be evaluated via a Timeliness property function of degree K. Assume that the functional behaviour of system is modelled via a network of Timed Automata.…”
Section: Definition 3 a Timeliness Property Of Degreementioning
confidence: 99%
“…al. [8] showed that the stream can be specified and verified using the real-time model checker UPPAAL [9]. However, the advantage of automatic verification was hindered by UPPAAL's restricted logic.…”
Section: To Appear In Proceedings Of Forte'03 Lncs C Springer-verlagmentioning
confidence: 99%
“…Finally, a burgeoning body of work exists pertaining to the formal verification of networked multimedia systems. Bowman et al [4] described multimedia stream as a timed automata, and verified the satisfaction of quality of service QoS properties including throughput and end-to-end latency. Sun et al [5] proposed a testing method for verifying QoS functions in distributed multimedia systems where media streams are modeled as a set of timed automata.…”
Section: Introductionmentioning
confidence: 99%